Analisis Perbandingan Desain Struktur Media Transplantasi Terumbu Karang Model Web Spider dan Model Pyramid - Sembiring, Kennedi; Harahap, Afivah Claura; Baswantara, Arief (Program Studi Teknik Kelautan Universitas Abdurachman Saleh Situbondo, 2025)
Coral transplantation is a marine ecosystem restoration technique used to improve the condition of damaged coral reefs, by accelerating the coral regeneration process in damaged areas. This study aims to test the effectiveness of the Web Spider coral reef transplantation model and the Pyramid model, in supporting the growth and survival of transplanted corals. The study was conducted on Pramuka Island, Seribu Islands for 2 months using Acropora tenuis coral fragments. The parameters observed included survival rate, corrosive rate, strength and stability of the structure, and environmental conditions of the waters such as temperature, brightness, and ocean currents. The results showed that the two transplantation models gave different results in several ways. The Web Spider model showed advantages in structural stability and ease of placement of coral fragments. In contrast, the Pyramid model was more effective in supporting vertical coral growth and more efficient in material use. The average survival rate of the Web Spider model reached 93% while the Pyramid model reached 100%. Based on the results of the analysis, it can be concluded that both models have their respective advantages, and the selection of models should be adjusted to local environmental conditions and rehabilitation goals.